STEM implementation in developing elementary students’ critical thinking skills in science as a response to PISA challenges - Nurfadliah Nurfadliah; Andi Nur Syarif Hidayatullah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study investigates the effectiveness of STEM-based science learning in improving elementary students’ critical thinking skills while addressing limitations in prior research designs. A quantitative approach with a one-group pretest–posttest design was employed to better capture learning gains. The participants were 30 fifth-grade students in Gorontalo City selected purposively based on academic characteristics. STEM instruction was implemented over four sessions using the 5E model. Data were collected through a validated and reliable critical thinking test, product assessment rubrics, and observation sheets. Data analysis included descriptive statistics, paired-sample t-tests, effect size calculation, and Pearson correlation tests. The results showed a significant improvement in students’ critical thinking scores after the intervention (p < 0.001) with a moderate effect size. Positive correlations were found among test scores, product performance, and instructional implementation. However, the findings are limited by the small sample size and short intervention duration. Overall, STEM-based learning demonstrates potential in fostering critical thinking skills in elementary science learning contexts.